Produção de ciclodextrina glicosiltransferase (CGTASE) por amostras de bacilus utilizando meios alternativos contendo substratos agroindustriais - Borba, Paula Patrícia (2013)
Microbial enzymes have a high biotechnological potential and are used in various industrial areas . The cyclodextrin glycosyltransferase ( CGTase , EC 2.4.1.19 ) is an enzyme with hablidade to convert starch into cyclodextrins ( CDs ) , being produced by various microorganisms , mainly bacteria of the genus Bacillus , being mainly applied in the food and pharmaceutical industries . Using the formulation of alternative means considered economical , has generated many studies to replace components of the traditional means of production , for substrates of industrial and agro-industrial residues of low cost and high value -added . In this connection , it was initially performed , selection of produce CGTase enzyme samples , Bacillus licheniformis (UCP 1021) were selected by halo formation characteristic in all conditions tested. Then , studies were conducted to formulate economic alternative means using agroindustrial waste , peel the potato ( Solanum tuberosum L ) and whey in the production of CGTase . In formulating means that the potato peel replaced starch , the concentrations used were 2.5 ; 5:10 g / L , being named A ¹ , A ² and ³ The . In the middle called B was replaced by potato peel peptone ( 10g / L ) in medium C was replaced by yeast extract, whey (5 g / L) medium and peptone- D was replaced by whey ( 5g / L). All assays for enzyme production occurred at 37 ° C , 150 rpm , 84 hours . The results showed that the standard production medium achieved a specific activity of 0.120 umol / mg in 24 hours, and it was found that all alternative media produced the enzyme , however, the midst called A ¹ showed the highest specific activity for B- CD ( 0.823 umol / mg) at 12 hours , suggesting that the use of cheap media containing organic residues , is a viable alternative for the production of various bioactive compounds used in microbial biotechnology process.